2015
DOI: 10.1002/term.2104
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-cell bone engineering in a validated preclinical animal model: precursors vs differentiated cell source

Abstract: The properties of osteoblasts (OBs) isolated from the axial skeleton (tOBs) differ from OBs of the orofacial skeleton (mOBs) due to the different embryological origins of the bones. The aim of the study was to assess and compare the regenerative potential of allogenic bone marrow-derived mesenchymal progenitor cells with allogenic tOBs and allogenic mOBs in combination with a mPCL-TCP scaffold in critical-sized segmental bone defects in sheep tibiae. After 6 months, the tibiae were explanted and underwent biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 17 publications
(19 reference statements)
0
39
0
Order By: Relevance
“…Moreover, the distribution of the newly formed bone in relation to the scaffolds (i.e. external, internal) can be quantified (Berner et al ., ). Saito et al .…”
Section: Bone Regeneration Xct Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the distribution of the newly formed bone in relation to the scaffolds (i.e. external, internal) can be quantified (Berner et al ., ). Saito et al .…”
Section: Bone Regeneration Xct Analysismentioning
confidence: 97%
“…Moreover, the distribution of the newly formed bone in relation to the scaffolds (i.e. external, internal) can be quantified (Berner et al, 2017). Saito et al (2015), for example, showed the influence of scaffold porosity in bone ingrowth within polymeric scaffolds and the increase of bone penetration over time.…”
Section: Ex Vivo Analysis Of Bone Regenerationmentioning
confidence: 99%
“…Two particular lines, MDA PCa 118a and MDA PCa 118b, were established as subcutaneous PDXs, providing a model of androgen-independent prostate cancer that induces a robust osteoblastic reaction in bonelike matrix and soft tissue (Li et al 2008). Improvements to bone metastatic PDXs include recent modifications using scaffold/matrices (Talukdar et al 2011;Holzapfel et al 2013Holzapfel et al , 2014Berner et al 2015) coupled with better imaging modalities to investigate the tumor biology (Tse et al 2015).…”
Section: Patient-derived Preclinical Modelsmentioning
confidence: 99%
“…Bone tissue engineering is an alternative solution for the repair of large bone defects, by providing a template to guide hard tissue regeneration. The standard tissue engineering approach includes the use of scaffolds, mesenchymal stem cells and growth factors, called the triangular concept, which will offer a bridging material guiding the regeneration of the new tissue [6,7]. Scaffolds used in bone regeneration are broadly classified into biological, mineral such as glass and ceramic materials and polymer scaffolds.…”
Section: Abstract: Bioactive Glass Regeneration Of Bone Defects Adimentioning
confidence: 99%